Logística de transporte: avaliando a qualidade do transporte público de passageiros em Araguaína - TO. - Costa, Regina Alves (Universidade Federal do Tocantins, 2020)
Transport Logistics studies the best modal to meet customer expectations, among the desirable requirements for the Public Passenger Transport System (STPP) are the following indicators: reliability, travel time, accessibility, comfort, convenience, safety and costs Of the tariff. The aim of this study is to analyze whether the STPP of Araguaína - TO, evaluates whether it offers quality based on the seven quality indicators based on the user's perception. Specifically, I sought to identify the user profile, II) Verify the STPP Quality Indicators and III) To propose improvements for the STPP in the town of Araguaína - TO. The study is classified as a field survey, based on a bibliographical review, with a quantitative and descriptive approach, were performed with users / clients of two concessionaires in different semesters of 2016, seeking to demonstrate the importance of each indicator, in order to map the factors that limit Functioning of the system. STPP involves broad issues in the social, economic and environmental spheres, for public and private managers to promote mobility is a challenge, to provide a quality STPP in the day to day of users / clients, promoting urban displacement and satisfying the interests of the community.